Intervenção judicial nas sociedades limitadas em face da liberdade de iniciativa - Leite, Marcelo Lauar (2013)
The judicial intervention in limited liability company goes through several issues of legislative and hermeneutics origin, based considerably on the small importance given to freedom of economic initiative by the participants in the process of formation and application of the law. In addition, Brazilian law, due to incompleteness, inconsistency or lack of valid grounds, put the judge in a procedural delicate situation. Being forced to judge, the judiciary faces severe uncomfortable interpretive situations, of which derive solutions of dubious constitutionality and affecting, significantly, the dynamics of business activity. In this context, and considering the limited liability company as an expression of free enterprise, corresponding to a lawful association of people in order to undertake economically, in exercise of his freedom of contracting and professional action, intended to be offered safe parameters of constitutionality for judicial intervention in limited liability company in the hypothesis of (i) transfer of corporate shares, (ii) attachment of corporate shares, (iii) dismissal of directors, (iv) appointment of judicial stakeholders, (v) exclusion of shareholders and (vi ) trespass. The hypothetical-deductive approach was adopted, building hypotheses to overcome the gaps and unconstitutionality of the law and subjecting them to tests, reviews, and comparisons with hypothetical facts and case law in order to determine the constitutional validity of the proposed solutions. The procedure aimed to reconcile the historical, comparative, dialectical and scientific methods. The roots of temporal institutes were researched as well as current solutions provided by national and compared law. From problematizations point, addressed by the constitutional interpretation of the law and jurisprudence, responses that bring out the unconstitutionality of certain conceptions were headed